INEUROPSYCHOPEDAGOGICAL INTERVENTION IN LEARNING PROBLEMS IN ATTENTION DEFICIT HYPERACTIVITY DISORDER - Silva, Rosana Moura da; Coutinho, Diogenes Jose Gusmão (Revista Ibero-Americana de Humanidades, Ciências e Educação, 2023)
It is at school that the child tests his physical, intellectual and emotional capacities, sharing the same physical space. In this context, the teacher is faced with challenging behaviors on the part of some students such as: disorganization, lack of motivation, difficulty in paying attention, problems in completing tasks, excessive agitation, difficulty in learning and sometimes aggressiveness, complicated cases, difficult to be worked. One of the most common cases is Attention Deficit Hyperactivity Disorder – ADHD. There is a need to seek support in extra-class professional specialties. It will be approached about the intervention of Neuropsychopedagogy in learning disorders resulting from ADHD.